A comparative move analysis of abstracts in a multidisciplinary conference proceedings: hard sciences vs soft sciences / Khairul Firhan Yusob and Ahmad Nazri Jelani - Yusob, Khairul Firhan; Jelani, Ahmad Nazri (Universiti Teknologi MARA, Pahang, 2022)
Abstract has received much attention as a genre by academics worldwide. A good abstract writing manages to attract more readers to read an article and has better opportunities for indexing and citation. Previous studies show how analyses have been done on abstracts written by native and non-native speakers of English as well as rhetorical moves that take place in abstracts. However, analyses of abstracts for crossed-disciplinary articles are rarely discussed. Thus, the present study which adapts a qualitative research design intends to study move types and patterns of abstracts in two different clusters: hard sciences and soft sciences, subsequently comparing them. 30 abstracts which had been sent to a multidisciplinary conference were collected and analysed using the Five-Move Model introduced by Hyland (2000). The areas under the field of soft sciences are Business, Education and Tourism while hard sciences included Chemistry, Biology and Forestry. The results show abstracts from hard sciences skipped some moves in the model, while abstracts from soft sciences followed nearly all moves from the model. However, it is interesting to note that the Move 5: Conclusion was often overlooked in both fields while Move 3: Method had been written fairly well by authors in both fields. Although there was only a slight difference, the data showed that authors in soft sciences were more interested to highlight their Findings (Move 4: Production), while authors in hard sciences focused more on the Move 2: Purpose move. Thus, the findings are expected to help authors especially from hard sciences cluster to become more aware of the academic convention of abstract writing and abide by the norms set in the scientific community.